Job Retention Schemes as a Long-Term Employment Policy Instrument - Torosyan, Alik («Տնտեսագետ» հրատ․)
The intervention of relevant government authorities is crucial when a critical situation arises, such as the coronavirus pandemic. They should not be underestimated; job retention schemes are the tools through which the governments shield the most vulnerable population from the adverse effects of massive dismissals. These schemes, which can be used in various ways, can be used to provide a timely and temporary fix to a developing problem in the form of a crisis, or they can be used as solutions that address issues such as structural unemployment in the long run. Across the globe, nations have embraced a variety of job retention schemes, which generally fall into three main categories: short-time work schemes, furlough schemes, and wage subsidy schemes. These schemes are shaped to suit each country since they should address particular problems and situations. The article explores how employment protection measures affected the unemployment trends during the COVID-19 pandemic, with this classification understandably steering reliance on job retention schemes as either temporary crisis responses or fundamental tools for a sustainable labor plan. More specifically, the article uses a panel model to understand better the relationship between the growth rates of COVID-19 cases and the fluctuations in the unemployment rate. The findings have revealed that governments implementing long-term job retention schemes observe much lower increases in unemployment compared to those relying on short-term solutions. Furthermore, in countries where job retention schemes have become part of sustainable economic development strategies, a higher level of public trust towards government activities has contributed to more stable consumer behaviour and improved economic stability.
Keywords: Macroeconomics